Reliable low power network protocol in IoT for agriculture field - Wong, Christopher Jin Soon (2024)
An Internet of Things (IoT) sensor network consists of sensor nodes which sample and send data to the base station. Agriculture is one sector which makes use of IoT sensor networks for collecting data on the growing environment of crops for farmers to perform adjustments for optimal crop growth. Deployment of IoT networks in agriculture use cases face multiple constraints, including power constraints. Thus, IoT systems from other industrial sectors cannot be used since they do not have the same constraints or requirements. Existing research in energy efficient network protocols have problems with reliability or weaknesses that make them unsuitable for direct use in agriculture use cases. This project suggests the design of a new reliable and energy-efficient network protocol for deployment in a simulated agriculture use case. This network protocol can be further split into three separate protocols, which are the application layer protocol, network layer protocol and data link layer protocol. The application layer protocol handles the sampling and caching of data, which saves energy by maximizing the data segment of packets sent. The network layer protocol simplifies the routing process based on connection tables from BNT. The data link layer protocol handles the Medium Access Control (MAC) of the mesh network efficiently using algorithms based on the Scheduling sub-cycle of the Fast, Adaptive, and Energy-efficient Multi-channel-multi-path (FAEM) protocol by Liew et al. The new network protocol will be tested in a simulation and benchmarked against other similar energy-efficient protocols to determine its capability.